Sick leave due to musculoskeletal disorders in the working population in a flower growing company in Colombia (2018)
Musculoskeletal disorders are one of the main causes of absenteeism, pain and disability in the world of work. Agricultural workers are predisposed to suffer from them because of the nature of their work. Objective: to describe the magnitude and costs of sick leave due to musculoskeletal disorders in workers of a Colombian flower company. Methods: a descriptive study was conducted, evaluating 3570 absences for medical reasons between January and December 2016. The episodes were grouped according to the International Classification of Diseases, and absenteeism rates were calculated. The total cost of absenteeism by DME was calculated according to the value of the working hour and days of absence of each worker. Results: there were 124 absences due to musculoskeletal disorders, 70.16% in females. The area with the highest absences is post-harvest with 45.16%. The total cost of absenteeism due to musculoskeletal disorders was estimated at $ 111,957,923 Colombian pesos (USD$ 38,600) for the study period. Conclusion: the high costs in this company are generated by alterations in the health conditions of the workers, clearly given by musculoskeletal disorders that must be approached immediately by the personnel in charge of the company implementing strategies of promotion and prevention in the workplace, in order to reduce these disorders. © 2018, Accion Medica S.A. All rights reserved.